HEALTH-ASSOCIATED INFECTIONS IN A HOSPITAL IN THE NORTH-EAST REGION OF ROMANIA -A MULTIDISCIPLINARY APPROACH - Nicoleta Luchian; Lucian Eva; Marius Gabriel Dabija; Daniela Druguș; Mădălina Duceac (Covrig); Geta Mitrea; Constantin Marcu; Mihaela Roxana Popescu; Letiția Doina Duceac (Romanian Society of Oral Rehabilitation, 2023)
Healthcare-associated infections (HAIs), also known under other names such as: nosocomial infections or intrahospital infections, are a major public health problem, affecting both patients, medical personnel involved in their care , and non-medical support personnel. Material and method: The study is retrospective, longitudinal, descriptive, observational, carried out in the Emergency Clinic Hospital, " Prof.Dr. Nicolae Oblu" from Iași in 2022 and included a batch of 375 hospitalized patients who contracted one or more healthcare-associated infections during hospitalization. Results: The analysis of multiple variables regarding the clinical-epidemiological and statistical data reveals an annual incidence rate of 4.46 %. Wards at risk such as neurosurgery and intensive care showed higher incidence rates (6.58%), with surgical wound infections, mechanical ventilation-associated pneumonia and urinary infections predominating. The etiological palette involved in the genesis of these infections was represented by multidrug-resistant (MDR) bacteria, with increased pathogenicity on immunosuppressed organisms. Conclusions: Our study is comparable to nationally and worldwide recorded data for the neurosurgical profile. Post-operative infections make it difficult for the body to recover in general and the neuromotor level. Our research draws attention to the detection of AIAM, as a permanent concern and responsibility of the entire medical body, as well as to the phenomenon of microbial antibiotic resistance, which is gaining momentum. Correct health management care would definitely lead to a decrease in the incidence of intrahospital infections and the growing phenomenon of microbial antibiotic resistance.